PELABELAN TOTAL TAK REGULER PADA BEBERAPA GRAF - Nugroho Arif Sudibyo; Siti Komsatun (Universitas Jenderal Soedirman, 2018)
For a simple graph G with vertex set V (G) and edge set E(G), a labeling Φ:V(G)U(G)→{1,2,...k} is called a vertex irregular total k- labeling of G if for any two diferent vertices x and y, their weights wt(x) and wt(y) are distinct. The weight wt(x) of a vertex x in G is the sum of its label and the labels of all edges incident with the given vertex x. The total vertex irregularity strength of G, tvs(G), is the smallest positive integer k for which G has a vertex irregular total k-labeling. In this paper, we study the total vertex irregularity strength of some class of graph.